Strategi Pedagang Kaki Lima Di Kawasan Kuliner Pantai Tak Berombak (Ptb) Kecamatan Turikale Kabupaten Maros - Nimpa, Bermanto Joyful (Jurnal Environmental Science, 2018)
This study Â aims to: (1) To identify and analyze the characteristics of street traders in Culinary Region Pantai Tak Berombak (PTB) Turikale District of Maros Regency. (2) To identify and analyze the factors that influence the development of enterprises in the Culinary Region Pantai Tak Berombak (PTB) Turikale District of Maros Regency. (3) To know and analyze the business development strategy carried out in order to develop optimally. Results showed (1) Characteristics of Street Vendors by age in Culinary Region Pantai Tak Berombak (PTB) Turikale District of Maros Regency dominated by the age group between 31-45 years. According to the education level is dominated by street vendors who had high school education. While the characteristics of street vendors by sex that most street vendors male. (2) Internal factors (knowledge and services) as well as external factors (location and personality) are factors that influence the development of enterprises Street Vendors Culinary Region Pantai Tak Berombak (PTB) Turikale District of Maros Regency. (3) Business development strategies that do street vendors can develop optimally, due to social capital, social networks and management.